WàCOLETIVO : Broderie, couture et crochet comme art contemporain dans l'espace public - WàCOLETIVO (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Visionarias de la perspectiva de género en el arte contemporáneo del Caribe colombiano - Flórez, Alexa Cuesta (Memoria y Sociedad, 2017)
La perspectiva de género en el arte del Caribe colombiano se puede contextualizar con el movimiento feminista planetario. La comparación se establece en las creaciones de mujeres artistas de esta región, ya que subvierten, manifiestan y revelan con denotada libertad expresiva, no solamente sus inquietudes intimistas, sino toda una serie de cuestionamientos a las condiciones que culturalmente se le han impuesto a la mujer en el Caribe. Son dos generaciones diferentes; las primeras, analizadas en esta entrega, pueden ser catalogadas como pioneras de la perspectiva de género en el arte colombiano. Las segundas, consolidan problemáticas en apuestas individuales, de manera diaspórica y cada vez más comprometidas con el movimiento social de mujeres. En ambos casos lo hacen a través de las artes visuales, audiovisuales, performáticas e híbridas. Estamos ante artistas vanguardistas, de las artes visuales y performáticas en el Caribe colombiano; preferimos llamarlas, en ambos casos, visionarias. Gender perspective in the Colombian Caribbean art can be contextualized within the worldwide feminist movement. The comparison is established in the artwork of female artists from this region, as they subvert, demonstrate, and reveal with poignant expressive freedom, not only their intimate concerns, but a whole series of questions to the conditions that have been culturally imposed on women in the Caribbean. They come from two different generations. The first generation, analyzed in this installment, can be defined as the pioneers of gender perspective in Colombian art. The second generation consolidates issues through individual pledges in a diasporic way and increasingly committed to the social women’s movement. Both generations do this through performative, hybrid, visual and audiovisual art. These are avant-garde artists of the visual and performative art in the Colombian Caribbean. We prefer to call them, in both cases, visionaries.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé